Seeking help when transgender: Exploring the difference in mental and physical health seeking behaviors between transgender and cisgender individuals in Ireland - Howell, Jamie (Int J Transgend, 2019)
Background: While there is growing awareness of the need to support the physical and mental wellbeing of transgender people, some may be reluctant to seek help from healthcare professionals. Little is understood about the mechanisms that influence help-seeking behavior in this group. Aims: This study aimed to compare transgender and cisgender participants in their likelihood to seek help for both physical and mental health conditions, and to explore whether this help-seeking behavior is predicted by a range of sociodemographic and psychological variables. Methods: 123 participants living in Ireland (cisgender= 67; transgender= 56) completed a questionnaire which included demographic questions, as well as measures of optimism (LOT-R), self-esteem (RSES), psychological distress (GHQ-12), attitudes towards seeking psychological help (ATSPPH-SF), and attitudes towards seeking help for a physical health problem (Attitudes Towards Seeking Medical Help Scale- Action/Intervention subscale). Associations between predictor variables and mental and physical health seeking were explored using correlation analysis and stepwise regressions. Results: Transgender participants were less likely to seek help for a physical health issue than cisgender participants, but did not differ in mental health help-seeking behaviors. Results suggest that this may be due to differences in optimism, self-esteem and psychological distress. Transgender participants had significantly lower optimism and self-esteem, which were two factors linked to poorer physical health seeking behaviors. Optimism also emerged as a significant predictor in mental health seeking behaviors. Discussion: The lack of a significant difference for mental health help-seeking between the transgender and cisgender participants is encouraging, as it suggests that there is less stigma surrounding mental illness than expected, however findings also contradict previous findings suggesting that physical health is less stigmatized. This could be due to stigma relating to gender-specific healthcare and suggests that healthcare professionals should acknowledge the specific healthcare needs and concerns among transgender individuals.